(untitled) (Research, Society and Development, 2021)
Introduction: Public drug procurement scheduling and procurement supply chains are becoming increasingly interconnected and structured. One of the professionals who work in these processes are the pharmacists, who, with their expertise in drug management, contribute to the effectiveness of these acquisitions, within the scope of the SUS. These activities demand an analytical and holistic perception, so that there is harmony between stock x acquisition x demand, avoiding waste and lack of drugs. Objective: To describe the importance of the pharmacist in the stages of drug selection and programming, within the cycle of Pharmaceutical Assistance in the SUS. Methodology: This is a literature review based on the search for electronic data such as PubMed, Virtual Health Library (BVS), Scielo and Ministry of Health catalog. Results and Discussion: We identified 09 studies that served as the basis for the development of this review. Studies indicate that drug programming and procurement activities within the Unified Health System (SUS) demand a holistic and analytical look in order to balance availability and quantity. Conclusion: The effective management in the selection and programming of medications within the SUS constitutes basic firsts aimed at promoting health through the distribution of medication and the care of public money. Current practices in the selection and programming of medication in the SUS have contributed to avoiding waste and the financial and environmental data that the lack of control could cause.